(untitled) (Ágora Journal, 2025)
In France, the Civil Code has often been subject to differing interpretations. It has been the object of self-celebration on the part of its promoters and veritable panegyrics on the part of its admirers. But it has also been denigrated by its detractors, either because they consider themselves to be its victims, or because they use their historical expertise to highlight its shortcomings, particularly in terms of labour and the protection of the workforce. These differing interpretations are fuelled by the periodic celebrations of the Civil Code: the centenary (1904), the hundred and fiftieth anniversary (1954) and the bicentenary (2004). The paper therefore examines the reception of the Civil Code by historians and by French legal doctrine.